The involvement of the noradrenergic system in the antinociceptive effect of cucurbitacin D on mice with paclitaxel-induced neuropathic pain - Park, Keun-Tae; Kim, Suyong; Choi, Ilseob; Han, Ik-Hwan; Bae, Hyunsu; Kim, Woojin (Frontiers in Pharmacology, 2023)
Paclitaxel is a taxol-based chemotherapeutic drug that is widely used to treat cancer. However, it can also induce peripheral neuropathy, which limit its use. Although several drugs are used to attenuate neuropathy, no optimal treatment is available, yet. In this study, the effect of cucurbitacin B and D on paclitaxel-induced neuropathic pain has been assessed. Multiple paclitaxel injections (cumulative dose of 8 mg/kg, i.p.) induced cold and mechanical allodynia from day 10 to day 21 in mice, and intraperitoneal administration of 0.025 mg/kg of cucurbitacin B and D attenuated both allodynia. However, as cucurbitacin B showed more toxic effect on noncancerous (RAW 264.7) cells, further experiments were conducted with cucurbitacin D. Cucurbitacin D dose dependently (0.025, 0.1, and 0.5 mg/kg) attenuated both allodynia. In the spinal cord, paclitaxel injection increased the gene expression of noradrenergic receptors (α1- and α2-adrenergic receptors), but not serotonergic receptors (5-HT1A and 3 receptors). The treatment of cucurbitacin D significantly decreased the spinal α1-, but not α2-adrenergic receptors, and the amount of spinal noradrenaline also downregulated. However, the tyrosine hydroxylase (TH) expression measured in the LC did not decrease significantly. Finally, cucurbitacin D treatment did not lower the anti-cancer effect of chemotherapeutic drug when co-administered with paclitaxel in CT-26 cell-implanted mice. Altogether, these results suggest that cucurbitacin D could be considered as a treatment option against paclitaxel-induced neuropathic pain.